Recognition or Restriction: Dialectics of Customary Criminal Law in the Paradigm of Indigenous Communities - Yoghi Arief Susanto; Mohammad Azzayyan Haykal Aditya; Ali Masyhar Mursyid; Edy Sujendro (IJCLS (Indonesian Journal of Criminal Law Studies), 2026)
The recognition of customary law in the New Criminal Code is like a double-edged sword: on one hand, it acknowledges customary law, but on the other, it imposes limitations cloaked in formalism. This study aims to identify customary criminal offenses that are still practiced in indigenous communities and to analyze the perspectives of indigenous communities regarding customary law as the basis for criminal punishment, unlike previous studies that were still conceptual in nature and lacked empirical support. Thus, this study presents an empirical perspective from indigenous communities regarding the recognition of customary criminal law in the New Criminal Code. The approach in this study is socio-legal, employing qualitative and interpretive analysis. The research was conducted using a purposive sampling method in Sembalun Village and Bangket Parak Village through in-depth interviews with traditional leaders and a literature review. This study concludes that the formalization of customary criminal law through local regulations has the potential to weaken its dynamic nature, given that, empirically, customary criminal law in Sembalun Village and Bangket Parak Village continues to evolve in response to the needs, values, and norms of the local community. Traditional leaders have responded positively to the recognition in the New Criminal Code, noting that customary law still holds greater binding power than state law. Therefore, the regulation of customary criminal law should be sufficiently affirmed in the general provisions of the Criminal Code as a guideline for judges in uncovering the living law within the community, without the need for further formalization through local regulations, to maintain a balance between state law and legal pluralism within Indonesian society.